2013
DOI: 10.1016/j.ejor.2012.12.019
|View full text |Cite
|
Sign up to set email alerts
|

On the structure of multiobjective combinatorial search space: MNK-landscapes with correlated objectives

Abstract: International audienceThe structure of the search space explains the behavior of multiobjective search algorithms, and helps to design well-performing approaches. In this work, we analyze the properties of multiobjective combinatorial search spaces, and we pay a particular attention to the correlation between the objective functions. To do so, we extend the multiobjective NK-landscapes in order to take the objective correlation into account. We study the co-influence of the problem dimension, the degree of non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
110
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 92 publications
(120 citation statements)
references
References 20 publications
10
110
0
Order By: Relevance
“…Intuitively, if this is true for each objective of a multi-objective problem, it will be true for the multi-objective problem itself. This assumption in the multi-objective case is supported empirically by some studies [6,15,21,37,44], and to some extent by the results of this paper.…”
Section: Alternative Algorithmic Components For Anytime Optimizationsupporting
confidence: 70%
“…Intuitively, if this is true for each objective of a multi-objective problem, it will be true for the multi-objective problem itself. This assumption in the multi-objective case is supported empirically by some studies [6,15,21,37,44], and to some extent by the results of this paper.…”
Section: Alternative Algorithmic Components For Anytime Optimizationsupporting
confidence: 70%
“…To this end, we plan to study the correlation between the main problem features and the algorithm performance through fitness landscapes analysis in multiobjective combinatorial optimization [35,51]. Last, we hope that the challenge proposed by multiobjective UBQP will gain the attention of other researchers.…”
Section: Discussionmentioning
confidence: 99%
“…The generation of correlated data follows a multivariate uniform law of dimension m [35]. In order to validate the behavior of the objective correlation coefficient experimentally, we conduct an empirical study for n = 18 in order to enumerate the decision space exhaustively.…”
Section: Problem Instancesmentioning
confidence: 99%
“…Later, Verel et al [15] conducted a study on the landscape of local optima in such problems. Verel et al [16] proposed to carry out a priori analysis of a problem by evaluating the problem size, its epistasis, the number of objectives and the correlation values between objectives, to suggest the best way to tackle it. They concluded that, depending on the problem features, different types of algorithms (scalar or Pareto approach) and sizes of the solution archive should be employed.…”
Section: Related Workmentioning
confidence: 99%